Perbedaan Kadar Trigliserida Pada Wanita Pre-menopause Dan Wanita Menopause Di Desa Labuhan Kecamatan Sepulu Kabupaten Bangkalan - Siti Rosa Lina; Gilang nugraha; Rosa Sastrawati (Universitas Nahdlatul Ulama Surabaya, 2020)
Triglycerides are the main fats in the body, formed in liver glycerol and di meal fats. The increase in fat in menopausal women is due to lack of physical activity that is not balanced with a healthy food intake that results in excess weight that affects the body's metabolism. So High Density Lipoprotein (HDL) decreased and Low Density Lipoprotein (LDL) became high and triglyceride levels also increased. Increased levels of triglycerides in the blood are risk factors for coronary heart disease (CHD). This study aims to find out if there are differences in triglyceride levels in 34 premenopausal women and 34 menopausal women in Labuhan Village, Sepulu District, Bangkalan Regency. This research is an analytical observational research with cross sectional approach (cut latitude). This research was conducted from May 2020 to July 2020. Examination of triglyceride levels is carried out using a photometer with GPO-PAP (glyserophosphate oxidase-paraaminophenazone) method. Based on the results showed that there is no difference between triglyceride levels in premenopausal women and menopausal women p-value = 0.083 average levels of triglycerides in premenopausal women namely 151.38 ± 31.40 mg / dL and in menopausal women of 174.91 ± 49.98 mg / dL.